Which factors predict tumor recurrence and survival after curative hepatectomy in hepatocellular carcinoma? Results from a European institution - Sascha Vaghiri; Dimitrios Prassas; Onur Mustafov; Sinan Kalmuk; Wolfram Trudo Knoefel; Nadja Lehwald-Tywuschik; Andrea Alexander; Levent Dizdar (BMC Surgery, 2024)
Abstract Background High tumor recurrence and dismal survival rates after curative intended resection for hepatocellular carcinoma (HCC) are still concerning. The primary goal was to assess predictive factors associated with disease-free (DFS) and overall survival (OS) in a subset of patients with HCC undergoing hepatic resection (HR). Methods Between 08/2004–7/2021, HR for HCC was performed in 188 patients at our institution. Data allocation was conducted from a prospectively maintained database. The prognostic impact of clinico-pathological factors on DFS and OS was assessed by using uni- and multivariate Cox regression analyses. Survival curves were generated with the Kaplan Meier method. Results The postoperative 1-, 3- and 5- year overall DFS and OS rates were 77.9%, 49.7%, 41% and 72.7%, 54.7%, 38.8%, respectively. Tumor diameter ≥ 45 mm [HR 1.725; (95% CI 1.091–2.727); p = 0.020], intra-abdominal abscess [HR 3.812; (95% CI 1.859–7.815); p < 0.0001], and preoperative chronic alcohol abuse [HR 1.831; (95% CI 1.102–3.042); p = 0.020] were independently predictive for DFS while diabetes mellitus [HR 1.714; (95% CI 1.147–2.561); p = 0.009), M-Stage [HR 2.656; (95% CI 1.034–6.826); p = 0.042], V-Stage [HR 1.946; (95% CI 1.299–2.915); p = 0.001, Sepsis [HR 10.999; (95% CI 5.167–23.412); p < 0.0001], and ISGLS B/C [HR 2.008; (95% CI 1.273–3.168); p = 0.003] were significant determinants of OS. Conclusions Despite high postoperative recurrence rates, an acceptable long-term survival in patients after curative HR could be achieved. The Identification of parameters related to OS and DFS improves patient-centered treatment and surveillance strategies.